Longitudinal relationship between loneliness and cognitive function among unmarried older adults in Malaysia: exploring gender disparities - Foong, Hui Foh; Ibrahim, Rahimah; Abdullah, Siti Farra Zillah; Bagat, Mohamad Fazdillah (John Wiley and Sons Inc, 2024)
Background: The status of being unmarried is commonly associated with a higher tendency for loneliness and cognitive impairment. However, it has yet to be determined whether there is a link between loneliness and cognitive function among unmarried older people. Therefore, this study used longitudinal data to determine the link between loneliness and cognitive function, and the subjects were unmarried community-dwelling older adults. Methods: The study follows up a sample of 733 unmarried older adults who were either never married, widowed, divorced or separated, from waves one and two of the ‘Neuroprotective Model for Healthy Longevity among Malaysian Older Adults’ study. The main statistical analysis used to answer the research question was the PROCESS macro (model 1) for SPSS. Results: The study found that increased loneliness was associated with a decline in cognitive function over a 3-year period. Additionally, gender moderated the link between loneliness and cognitive function, with this association being particularly prominent in older men. Conclusions: Loneliness among unmarried older people should be given attention as it could lead to deteriorating cognitive function. Notably, older men experience a more substantial impact of loneliness on cognitive function than women. Therefore, special attention should be focused on this population, and more social services should be developed to reduce the incidence of cognitive impairment, improve their quality of life, and promote successful ageing.